Conservação da biodiversidade, cultivo e produção de erva-mate no município de São Mateus do Sul - Paraná - Luiz, Ricardo Gomes (2017)
The conservation of biodiversity is an issue of an international agreement promoted by the United Nations, which records the reduction of diversity of species and ecosystems throughout the planet. Brazil has been a signatory to the Convention on Biological Diversity since 1994. Its responsibility extends to biomes such as the Amazon, Pantanal, Cerrado, Caatinga, Campos Sulinos and the Atlantic Forest, in addition to marine areas. This dissertation is inserted in the context of the Araucaria Forest, located in the south of Brazil. Associated with the Atlantic Forest, in this ecosystem there are trees like araucaria-pine, imbuias, ipês, canelas and yerba-mate, besides a varied fauna. In the process of exchanging forest for cultivated areas, it is necessary to create strategies to conserve the remaining areas, as is the case of those existing in the municipality of São Mateus do Sul, in Paraná State. The arguments to support this context of loss of biodiversity and externalities come from the Science, Technology and Society (STS) studies, which develop relevant concepts to establish the relations between human actions and the maintenance of biodiversity. The general objective of the study is to analyze the conflicts, contradictions and consensuses that interfere in the conservation of the biological diversity and in the forms of cultivation of yerba mate produced in the municipality of São Mateus do Sul. The research is qualitative, descriptive and bibliographic. The methodological procedures use the analysis of perception and data collection through observation, interviews and testimonials. In the perspective of the conservation of the biodiversity of the Araucaria Forest with the quality of the yerba-mate cultivated in the region, based on conflicting and contradictory behaviors, companies and producers made technical and scientific associations not satisfactory to the expectations of the dissertation. However, there are contributions and potentialities of agreements and consensus of the actors and concepts of the STS studies that allowed to create different looks for the researcher about his object of study. Therefore, the data collection and analysis were opening fields to enter into considerations between survival and respect for the environment. In this way, it is concluded that there is a continuous social construction of actors that can bring to light other concepts that contrast with the determinism and utopia of gains and losses.